HUBUNGAN KONSUMSI MAKANAN SIAP SAJI DENGAN KEJADIAN PENYAKIT DIARE DI SD NEGERI 101800 KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Tarigan, Herri Novita (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Elementary school -age children eating fast food is a problem that is a major concern in the community, especially foods that contain dangerous chemicals in the canteen, and food sellers around the school are important agents that make children eating unhealthy foods. and cause diarrhea for children. This study aims to The Relationship Between Fast Food Consumption And Incidence Of Diarrhea In Sd Negeri 101800, Deli Tua Sub District, Deli Serdang District. This a study using analytical observational design with a cross sectional study approach. The population of this study was a student of SD Negeri 101800 totaling 294 students with 75 student as sample. Sampling used in this study was stratifield random sampling. Data analysis use Chi Square. The results of this study indicate the distribution of the frequency of consumption of fast food 75 respondents (100%), as many as 43 students (57.3%) have a high level of consumption of fast food and there are 32 students (42.7%) with the level of consumption of fast food The low one. The frequency distribution of 44 students diarrhea (58.7%) experienced diarrhea and as many as 31 students (41.3%) did not experience diarrhea. Chi Square test results obtained significant data with P-value = 0,000 p-value <0.05. It can be concluded from the results of this study, that there is a relationship of consumption of fast food with the incidence of diarrhea in SD Negeri 101800 Deli Tua Sub District, Deli Serdang District in 2023. Suggestions from the results of this study are that teachers are expected to provide support so that children have good snack habits and pay more attention to the cleanliness of places selling snacks around or outside school.